On perfect fluid spacetimes obeying Gray’s decompositions - De, Uday Chand; Altay Demirbag, Sezgin; Özen Zengi̇n, Füsun (World Scientific Pub Co Pte Ltd, 2024)
In this work, perfect fluid spacetimes obeying Gray’s decompositions have been studied. In the first part, after a brief summary about Gray’s decompositions used in this study, we work on properties of perfect fluid spacetimes obeying these decompositions. The results are obtained for different subspaces of a perfect fluid spacetime. Thereafter, we present the characterizations of these spacetimes by proving some theorems.
Keywords: Local Riemannian geometry; Global differential geometry of Lorentz manifolds, manifolds with indefinite metrics; Local differential geometry of Lorentz metrics, indefinite metrics; Local differential geometry of Hermitian and Kählerian structures; Gray's decomposition; energy-momentum tensor; Applications of local differential geometry to the sciences; GRW-spacetime; Linear and affine connections; RW-spacetime; perfect fluid spacetime